THE ROLE OF DIALOGUE IN PREVENTING AGGRESSION AT SCHOOL - Kozubska, Alicja (The Modern Higher Education Review, 2021)
Authentic dialogue is one of the most mature forms of interpersonal contacts, and at the same time it grows only on the ground of proper interpersonal relations. The role of dialogue in the field of education is more and more frequently recognized as a way of regulating contradictions and limiting aggressive behaviour directed against others or oneself. Dialogue, as a consequence of the meeting of entities (including educational ones), is a form of contact that brings certain values connecting these entities. We can learn the dialogical form of contact mainly by experiencing it. In the case of educational dialogue, it requires defined competencies on the part of teachers who are to educate to dialogue, respecting the rules of social relations. Therefore, conducting an educational dialogue may be treated as a specific prophylactic action preventing pathological phenomena, including aggression among children and adolescents. The notion of aggression, its typologies and reasons, as well as the relation to the lack of dialogue at school have been described in the article below.